The relationship between claimed restorations and future restorations in children and adolescents: An observational follow-up study on risk categories for dental caries. - Riët Hummel (Public Library of Science (PLoS), 2021)
Various models are available to assess caries risk in individuals. In general past caries experience is considered as the best single predictor for future caries development in populations. Likewise, recent restorations have been used to predict future restorations. We aimed to evaluate a classification model for risk categories for dental caries in children based on claims data from Dutch healthcare insurance company Zilveren Kruis. The baseline caries risk categories were derived from the number of claimed restorations in two baseline years (2010 through 2011). These categories were defined as low (no new restorations), moderate (1 new restoration), and high (2 or more new restorations). First, we analyzed the relationship between baseline caries risk categories and the number of new restorations during 3 years of follow-up (2012 through 2014). Secondly, we used negative binominal two-level analyses to determine the accuracy of our classification model in predicting new restorations during follow-up. Thirdly, we reclassified the participants after 3 years and determined the changes in the categorization. We included insurance claims data for the oral healthcare services in 28,305 children and adolescents from 334 dental practices for the period 2010-2014. At baseline, 68% of the participants were in risk category low, 13% in moderate and 19% in high. The mean number of new restorations during follow-up was 0.81 (SD 1.72) in baseline risk category low, 1.61 (SD 2.35) in moderate, and 2.65 (SD 3.32) in high. The accuracy of the multivariate model for predicting 0/>0 restorations was 50%. After 3 years, 60% of the study participants were in the same risk category, 20% were in a lower, and 21% in a higher risk category. Risk categories based on claimed restorations were related to the number of new restorations in groups. As such, they could support planning and evaluation of oral healthcare services.